Assessment of sowing dates and plant densities using CSM-CROPGRO-Soybean for soybean maturity groups in low latitude. (5th December 2020) - Sampaio, L. S.; Battisti, R.; Lana, M. A.; Boote, K. J.
Abstract: Crop models can be used to explain yield variations associated with management practices, environment and genotype. This study aimed to assess the effect of plant densities using CSM-CROPGRO-Soybean for low latitudes. The crop model was calibrated and evaluated using data from field experiments, including plant densities (10, 20, 30 and 40 plants per m 2 ), maturity groups (MG 7.7 and 8.8) and sowing dates (calibration: 06 Jan., 19 Jan., 16 Feb. 2018; and evaluation: 19 Jan. 2019). The model simulated phenology with a bias lower than 2 days for calibration and 7 days for evaluation. Relative root mean square error for the maximum leaf area index varied from 12.2 to 31.3%; while that for grain yield varied between 3 and 32%. The calibrated model was used to simulate different management scenarios across six sites located in the low latitude, considering 33 growing seasons. Simulations showed a higher yield for 40 pl per m 2, as expected, but with greater yield gain increments occurring at low plant density going from 10 to 20 pl per m 2 . In Santarém, Brazil, MG 8.8 sown on 21 Feb. had a median yield of 2658, 3197, 3442 and 3583 kg/ha, respectively, for 10, 20, 30 and 40 pl per m 2, resulting in a relative increase of 20, 8 and 4% for each additional 10 pl per m 2 . Overall, the crop model had adequate performance, indicating a minimum recommended plant density of 20 pl per m 2, while sowing dates and maturity groups showed different yield level and pattern across sites in function of the local climate.